Analisis Pengajuan Soal Matematika Siswa SMP Ditinjau Dari Gaya Kognitif Fast Accurate dan Slow in Accurate - Ana Rahmawati (Universitas PGRI Madiun, 2017)
this research is a descriptive research with qualitative approach as it is meant to describe question submission of Junior High School students seen from cognitive style, namely; fast-accurate style cognitive style and slow-inaccurate style. The data collection method used in this research are test and interview. The data credibility is then tested through triangulation of time. the result shows that the description of question submission submitted by subject of fast-accurate are; most of the questions submitted are mathematical questions except few of them are not, the questions submitted by the subject are varied, most of the questions submitted are from visual information, all questions submitted can be solved, the questions submitted by the fast-accurate subject are balance between medium and high difficulty, the solution of all questions submitted are correct. The submission of questions done by slow-inaccurate group are: most of the questions submitted by slow-inaccurate group are mathematical questions except one, the questions submitted are varied, the questions submitted from visual and verbal information are balance where 6 questions are from visual and the other 6 are from verbal, most of the questions can be solved except one, most of the questions are in medium level of difficulty, most of the questions can be solved correctly except question number 9 which can be solved as the information given are not enough to solve the problem.